Criterios de eficiencia y buenas prácticas en los procesos de concentración de las organizaciones de participación - Bel Durán, Paloma; Martín López, Sonia (REVESCO. Revista de Estudios Cooperativos, 2008)
In the study of Corporate Social Responsibility in cooperative societies it is necessary to identify its areas of application, as well as the groups of interest, its particular relation with the company and the treatment of the efficiency as managerial principle and as combination of efforts towards the Social Responsibility. This work sets out to study Corporate Social Responsibility for the case of cooperative societies, on one hand from the internal sphere or core that of the definition of Corporate Social Responsibility would pay attention to the workers, the customers and the suppliers, this is to the associates, and on the other hand from a wider sphere that would take in account the competitors, the local community, the environment and the society in general. For it, it is analyzed as fundamental requirements in the internal area, the efficiency in the participation of the associates in the managerial flows, and in the external area, the managerial concentration of the cooperative societies, as well as the variables that are modified in the processes of managerial concentration to obtain values that increase the good government and the Corporate Social Responsibility. Finally, it is determined the effects that the processes of concentration have in the determination of the value of the Social Responsibility in the cooperative societies.